Systemic lupus erythematous as an unusual cause of intussusception in Sudanese woman: A case report - Salwa Dafa Allah Salih Mohammadeen (Wiley, 2021)
Abstract Abdominal pain does have a wide differential diagnosis, however, gastrointestinal involvement is not unusual in SLE, and this report is to describe an unusual case of intussusception due to SLE in a Sudanese woman.